O coordenador pedagógico e os saberes revelados nas práticas formativas: possibilidades na constituição de seu papel de formador - Scandalo, Priscilla Pereira (2023)
The present work starts from the proposition that the PC is responsible for the process of continuing education, in the school context, being the great articulator of pedagogical practices, acting together with teachers in their formative role. The numerous demands to which the PC is exposed, in its professional routine, can divert it from its main function and interfere in the constitution of its professional identity. Then came the desire to investigate, through the lens of the pedagogical coordinator, the knowledge revealed in training practices. It is important to emphasize that the knowledge of the PC, in addition to what is assigned to it in the exercise of its function, are constituted of their personal experiences, their social and cultural context, expressed in their professional identity. Thus, this research had as general objective to analyze how the pedagogical coordinator understands his professional identity, and expresses this constitution in his performance, in the practices of teacher training in service. As theoretical references were used studies on the historical course of teacher training in service and its critical-reflective perspective, the constitution of the identity of the PC and its formative role, and the teaching knowledge that subsidize the professional practice, studies of Almeida (2001; 2010; 2014; 2018), Dubar (2005), Freire (1987; 1991; 1992; 1997; 2000), Imbernón (2011), Marcelo (1999; 2009), Nóvoa (1992; 2013), Placco (2008; 2014), Placco and Souza (2006; 2017; 2018), Placco, Almeida and Souza (2011;2012), Saviani (2009), Tardif (2014), among others. The research was based on a qualitative approach, considering the relevance of the participation of the application of an online questionnaire and the realization of semi-structured interviews with coordinators working in the public schools of Elementary School I, in a city of Greater São Paulo. The results obtained, organized into three categories of analysis and supported by the theoretical references, revealed a high demand for assignments, assumed by the PC, which even reporting their role as the main function, and having as objective planning and implementation of their training practices, complications and administrative demands hinder their performance. In addition, the interviewees' reports, regardless of the time of experience in coordination, highlighted the importance of interacting and contributing to the teaching collective. Depending on this context, various knowledge is mobilized by the PC, such as: experiential, relational, curricular, vocational training, etc, but they need to be questioned, expanded and re-meaning, in the processes of continuous formation and self-formation. It was found that these training processes for the PC, for the most part, are focused on improving teaching practice and implementing educational projects, revealing the need for formative processes that favor the constitution of their professional identity, skills to articulate, form and transform